Strategi Guru PAI dalam Menerapkan Kedisiplinan Shalat Siswa SD IT Mutiara Kota Pariaman - Bella Shantika; Rahmi Wiza (FONDATIA, 2022)
The strategies used by Islamic education teachers can create students who are disciplined in praying. The title of this research is "Islamic Education Teacher's Strategy in Implementing the Discipline of Student Prayers of SD IT Mutiara in Pariaman city" aims to describe the Islamic education teacher's strategy in implementing the discipline of zuhur prayer of SD IT Mutiara students in Pariaman city, describe the effect of Islamic education teacher's strategy in implementing student prayer discipline at home, describe the Islamic Education teacher's solution in overcoming the obstacles experienced by parents in implementing student prayer discipline at home. This research uses a qualitative method with a case study approach. The data source of this research is from fourteen informants consisting of the principal, three Islamic education teachers, five students, five parents of students using purposive sampling technique. The results of this study are (1) There are five strategies used by Islamic education teachers, namely a. Motivating students, b. Through learning in class, c. Teacher supervision, d. Teachers participate in prayer with students, e. Teachers participate in prayer with students, e. Teachers participate in prayer with students. Teachers participate in prayer with students, e. Give rewards and punishments. (2) Some students have been disciplined in praying at home, but some students are still less disciplined in praying at home. (3) PAI teachers have solutions to overcome the obstacles experienced by parents at home, namely a. Providing strategies, b. Providing motivation, c. Reminding students.